2004
DOI: 10.1007/s00198-004-1754-7
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and trabecular bone mineral density in transsexuals after long-term cross-sex hormonal treatment: a cross-sectional study

Abstract: The aim of this study was to explore the effect of long-term cross-sex hormonal treatment on cortical and trabecular bone mineral density and main biochemical parameters of bone metabolism in transsexuals. Twenty-four male-to-female (M-F) transsexuals and 15 female-to-male (F-M) transsexuals treated with either an antiandrogen in combination with an estrogen or parenteral testosterone were included in this cross-sectional study. BMD was measured by DXA at distal tibial diaphysis (TDIA) and epiphysis (TEPI), lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 35 publications
5
80
0
Order By: Relevance
“…The latter long-term study also demonstrated higher serum levels of bone resorption markers, which is in agreement with the current results (9). However, not all studies in trans men documented higher bone resorption (11,19,20). Furthermore, our observations on areal bone parameters correspond with previous research reporting a preservation of aBMD during the first years of testosterone treatment (11,12,13,21,22) as well as after a longer exposure time and SRS (up to 10 years) in trans men (19,20,23).…”
Section: Discussionsupporting
confidence: 87%
“…The latter long-term study also demonstrated higher serum levels of bone resorption markers, which is in agreement with the current results (9). However, not all studies in trans men documented higher bone resorption (11,19,20). Furthermore, our observations on areal bone parameters correspond with previous research reporting a preservation of aBMD during the first years of testosterone treatment (11,12,13,21,22) as well as after a longer exposure time and SRS (up to 10 years) in trans men (19,20,23).…”
Section: Discussionsupporting
confidence: 87%
“…In dialysed renal insufficiency patients, earlier research has provided evidence for the preservation of cortical bone (measured at T-DIA) with continuous ambulatory peritoneal dialysis compared to haemodialysis, possibly in relationship with the higher residual renal function observed in the former [18]. Furthermore, in the very specific population of female to male transsexuals under long-term hormonal treatment, the effect of androgens on cortical bone was shown in a crosssectional study measuring BMD at the tibial sites [10]. In idiopathic renal stone formers, BMD was previously shown to be reduced at LS, Ward's triangle, T-EPI and T-DIA, whereby the latter two showed the largest magnitudes of change [19].…”
Section: Discussionmentioning
confidence: 99%
“…For tibial BMD, the local Bern normative database derived from 400 healthy Caucasian women living in the area of Bern, Switzerland served as reference [10]. Peak bone mass (mean value±SD of the age group 20 to 29 years) in this female reference population is 1.278±0.116 g/cm 2 (T-DIA), and 0.763±0.094 g/cm 2 (T-EPI), respectively.…”
Section: Questionnaires and Bmd Measurementsmentioning
confidence: 99%
“…The effects of androgens on cortical bone are better documented, even if not completely defined. Several studies have demonstrated that androgens contribute to periosteal bone accrual in men (78) as well as in male rodents (79) and that androgens induce the differences in bone size between men and women (80). Androgens may act on the periosteal surface by increasing periosteal bone formation.…”
Section: Dhtmentioning
confidence: 99%
“…Thus the effects of the aromatization of androgens on cortical bone cannot be excluded. In any case, however, some preliminary evidence speaks in favor of a key role for estrogen on cortical bone in men too; several studies have shown a positive correlation between androgens and cortical thickness (10,78,79,81), while the FEI seems not to be associated with cortical bone size in young men during pubertal bone accrual (85). This issue remains poorly understood at the moment and a link to the activity of a-or b-estrogen receptors and their tissue distribution might even be supposed, since periosteal apposition is induced by a-estrogen receptor, while its inhibition is mediated by the b-estrogen receptor (29,46).…”
Section: Dhtmentioning
confidence: 99%